THE EFFECT OF TRANSFORMATIONAL LEADERSHIP STYLE AND MOTIVATION ON EMPLOYEE PERFORMANCE OF PT. PLN (PERSERO) UPP JBTB 2 - Muhammad Putra Bagus Firmansyah; Is Fadhilah (Suluh Adiluhung Publisher (SAPub), 2025)
Responding to the dynamics of competition in the energy industry that continues to this day, both private institutions and the government are required to improve their performance in various sectors. This study aims to analyze the influence of transformational leadership style and motivation on the performance of employees at PT. PLN (PERSERO) UPP JBTB 2. The approach used is quantitative, with a survey method utilizing a 4-point Likert scale questionnaire. This study involved a sample of 32 respondents from PT. PLN (PERSERO) UPP JBTB 2. Normality testing was conducted using the Kolmogorov-Smirnov test through IBM SPSS Statistics 30 with a significance level of 0.05. The results indicate that transformational leadership style and motivation have a positive and significant effect on employee performance.